Piston ring-cylinder liner tribology investigation in mixed lubrication regime: part I-correlation with bench experiment. Issue 6 (14th September 2015) - Ba, Lin; He, Zhenpeng; Guo, Lingyan; Chiang, Young; Zhang, Guichang; Lu, Xing
Abstract : Purpose: – The purpose of this paper is to improve the environment and save energy, friction reduction, lower oil consumption and emissions demand that are the chief objectives of the automotive industry. The piston system is the largest frictional loss source, which accounts for about 40 per cent of the total frictional loss in engine. In this paper, the reciprocating tribometer, which is updated, was used to evaluate the friction and wear performances. Design/methodology/approach: – An alternate method is introduced to investigate the effect of reciprocating speed, normal load, oil pump speed and ring sample and oil temperature on friction coefficient with the ring/liner of a typical inline diesel engine. The orthogonal experiment is designed to identify the factors that dominate wear behavior. To understand the correlations between friction coefficients and wear well, different friction coefficient results were compared and explained by oil film build-up and asperity contact theory, such as the friction coefficient over a long period and averaged the friction coefficient over one revolution. Findings: – The friction coefficient changes little but fluctuates with a small amplitude in the stable stage. The sudden change of frequency, load and stroke will lead to the oil film rupture. The identification for the factors that dominates the wear loss is ranged as F (ring sample) >, E (oil sample) >, B (stroke) >, D (temperature) >, A (load) >, G (liner) > and C (frequency). Originality/value: – This paper develops and verifies a methodology capable of mimicking the real engine behavior at boundary and mixed lubrication regimes which can minimize frictional losses, wear, reduce much work for the experiment and reduce the cost. The originality of the work is well qualified, as very few papers on a similar analysis have been published, such as: The friction coefficient values fluctuating in the whole stage may be caused by the vibration of the system; suddenly, boundary alternation may help the oil film to form the lubrication; and weight loss mainly comes from the contribution of the friction coefficient value fluctuation. The paper also found that the statistics can gain more information from less experiment time based on a design of experiment.